ANALISIS PROSES PELAKSANAAN KONSTRUKSI STRUKTUR PONDASI PADA PROYEK PEMBANGUNAN CRUDE PALM OIL (CPO) STORAGE TANK PT PP LONDON SUMATRA INDONESIA PALEMBANG, SUMATERA SELATAN - , SUPRIYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Foundation is the most important substructure of building construction, because of it, there are many things which become considering not only in designing, but also field implementation of foundation construction. This studying animed to analyze storage tank foundation implementation in the field and this aimed to comparing between theories and regulation in designing that writer had been studied in the college too. Collecting data methode had been done by observation in the field directly, consultation with consultant and/or contractor and literature studying also. According to analyzing we can conclude that there are some construction realization process, such as soil investigation, pilling, pile cap construction, fromwork installing, and concrete casting.